The The Moderating Role of Religious Moderation in Shaping Tolerance Attitudes among Generation Z in the Digital Religious Landscape - Mualim Mualim (Khazanah Theologia, 2024)
Purpose: This study aims to examine the influence of religious moderation attitudes on religious tolerance attitudes among Generation Z in Kuningan Regency, particularly in the context of exposure to religious issues circulating on social media. The primary focus is to understand how the value of moderation can moderate the impact of digital religious issues—such as radicalism, moderate clerics, and foreign cultural influences—on the formation of tolerant attitudes, considering that Generation Z is the dominant age group in Indonesia’s population and highly active in the digital sphere. Methodology: This research employs a quantitative approach with a survey design involving 360 respondents from among Generation Z students in Kuningan Regency. Data were collected using a closed-ended Likert-scale questionnaire and analysed using multiple linear regression and moderated regression analysis (MRA) to assess both direct effects and the moderating role of religious moderation attitudes. Instrument validity and reliability were tested using the KMO measure, Bartlett’s Test, and Cronbach’s Alpha. Findings: The findings reveal that out of five examined religious issues, three—foreign culture, moderate clerics, and radicalism—have a direct influence on tolerance attitudes, while the other two do not show significant effects. However, when moderated by religious moderation attitudes, all five issues exhibit significant effects on tolerance attitudes. The most notable result appears in the case of radicalism, where a strong moderate attitude serves as an effective shield against the influence of extremist narratives. These results indicate that religious moderation plays a critical cognitive role in shaping how young people engage with complex religious content online. Research Implications: The study suggests that religious moderation can function as a cognitive filter for Generation Z in navigating digital religious content, highlighting the need to strengthen digital religious literacy based on moderation values through both formal and informal education, and through collaborative efforts among religious institutions, digital media, and youth communities. Originality/Value: This study contributes new insight to the field of digital religiosity by positioning religious moderation as a moderating variable—a perspective that has been largely unexplored in previous research. It enhances understanding of how internal values can function in filtering and responding to religious issues in social media, offering a contextually relevant framework for Indonesia’s socio-religious landscape.